Optimization and In Vitro Characterization of Telmisartan Loaded Sodium Alginate Beads and Its In Vivo Efficacy Investigation in Hypertensive Induced Animal Model - Ubaidulla Uthumansha; Kousalya Prabahar; Dilli Bhai Gajapathy; Mohamed El-Sherbiny; Nehal Elsherbiny; Mona Qushawy (MDPI AG, 2023)
Background: Antihypertensive drug telmisartan (TEL) belongs to BCS class II, which is characterized by low water solubility and, consequently, low oral bioavailability. Gastroretentive systems may overcome the problems associated with low solubility of TEL and incomplete absorption by localizing the drug release in the stomach. The purpose of this study was to prepare TEL-loaded, oil-entrapped, floating alginate beads with the intent of enhancing the oral bioavailability of TEL for the treatment of hypertension. Methods: For the formulation and optimization of seventeen formulations of TEL-loaded oil-entrapped floating alginate beads, a central composite design was utilized. The concentration of sodium alginate (X1), the concentration of cross-linker (X2), and the concentration of sesame oil (X3) served as independent variables, whereas the entrapment efficiency (Y1), in vitro buoyancy (Y2), and drug release Q6h (Y3) served as dependent variables. Using the emulsion gelation method and calcium chloride as the cross-linking agent, different formulations of TEL alginate beads were produced. All formulations were evaluated for their entrapment efficiency percentage, in vitro buoyancy, and in vitro drug release. The optimal formulation of TEL alginate beads was prepared with and without oil and evaluated for entrapment efficiency percentage, in vitro buoyancy, swelling ratio, average size, and in vitro drug release. Using scanning electron microscopes, the surface morphology was determined. Using IR spectroscopy, the compatibility between the ingredients was determined. In vivo evaluation of the optimized formulation in comparison to the free TEL was done in hypertension-induced rats, and the systolic blood pressure and all pharmacokinetic parameters were measured. Results: The prepared beads exhibited a high entrapment efficiency percentage, in vitro buoyancy, and prolonged drug release. TEL was compatible with other ingredients, as approved by IR spectroscopy. The prepared TEL beads were spherical, as shown by the SEM. The relative bioavailability of TEL-loaded oil-entrapped beads was 222.52%, which was higher than that of the pure TEL suspension. The prepared TEL beads formulation exhibited a higher antihypertensive effect for a prolonged time compared to pure TEL suspension. Conclusions: It can be concluded that this innovative delivery method of TEL-loaded oil-entrapped beads is a promising tool for enhancing drug solubility and, thus, oral bioavailability and therapeutic efficacy, resulting in enhanced patient compliance. Furthermore, the in vivo study confirmed the formulation's extended anti-hypertensive activity in animal models.